Factors associated with patient safety implementation based on safety attitudes questionnaire in accredited hospital Jambi City Indonesia - Buhari, Basok; Machmud, Rizanda; Dorisnita, Dorisnita (Riset Informasi Kesehatan; Vol 8 No 2 (2019): Riset Informasi Kesehatan, 2019)
A bstrac t Background : The Nursing service are influenced by the behavior nurses in implementation of patient safety the Contributes to adverse event or incident patient safety in accredited public hospital. This study aims to analyses most dominant determinant factors associated with patient safety implementation based on safety attitudes questionnaire (SAQ) in accredited hospital. Methods : This study is a cross sectional study with quantitative method conducted on nurses who work in accredited hospital. Samples of 190 nurses were included in this study by using proportional random sampling technique. The data were analyzed by using multiple logistic regression with backward LR method. Results : Total 190 participant were (22.1%) males and 148 (77.9%) females. Most participant had completed Diploma of vocational education 157 (82.6%). The most dominan factors associated with implementation of patient safety base on Safety Attitude Questionnaire is the work environment factor (p 0.001; OR 3.187). Conclusion : It is proven that a good work environment factor will improve the behavior of nurses in implementing patient safety. This research recommends to develop policy toward evaluation effort of implementation patient safety, as well as evaluation of all nursing procedures in terms of patient safety consideration to external or internal work environment. Key Word: Accredited Hospital; Patient Safety; Safety Attitude Questionnaire (SAQ), Work Environment